EXPERIMENTAL RESEARCH METHODOLOGY BOUNDARY DEFORMATIONS FIBER REINFORCED CONCRETE BEAMS TEE PROFILES AT OBLIQUE DEFORMATION - , М. О. (Municipal economy of cities (Technical science), 2013)
The method of experimental researching of non-uniplaner bended reinforced concrete T-beams are considered in this article. It’s possible experimentally to establish the dependence of the limit strain of concrete compressed zone from the angle of the power plane, area reinforcement and its location using this method.